2019
DOI: 10.1037/xge0000528
|View full text |Cite
|
Sign up to set email alerts
|

Social media and depression symptoms: A network perspective.

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
242
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 246 publications
(260 citation statements)
references
References 48 publications
15
242
3
Order By: Relevance
“…An early group of experimental and correlational studies found that while disconnection drives the use of Facebook, connection results from Facebook use [52]. This does not fall in line with those studies finding negative relations in both directions [1,22,71], only in the direction of social media use decreasing well-being [33] or only in the direction of loneliness leading to Facebook use [55]. It is therefore clear that more work considering bidirectional effects needs to be completed before true effects become evident.…”
Section: Small Negative Associations Between Screens Social Media Anmentioning
confidence: 92%
See 1 more Smart Citation
“…An early group of experimental and correlational studies found that while disconnection drives the use of Facebook, connection results from Facebook use [52]. This does not fall in line with those studies finding negative relations in both directions [1,22,71], only in the direction of social media use decreasing well-being [33] or only in the direction of loneliness leading to Facebook use [55]. It is therefore clear that more work considering bidirectional effects needs to be completed before true effects become evident.…”
Section: Small Negative Associations Between Screens Social Media Anmentioning
confidence: 92%
“…[5]. It is therefore important to conduct more longitudinal work [10,14,24] with more diverse time frames [5] ranging from short-term experience sampling [1] to long-term annual studies [71].…”
Section: At-risk Populationsmentioning
confidence: 99%
“…These factors tap into important aspects of psychosocial functioning, relevant to MH in multiple ways. They are crucial predictors or boundary conditions for MH (e.g., social support as a buffer that increases PWB; Burke & Kraut, 2016) or link CMC indirectly to more central MH indicators (e.g., stress as a risk factor for depressive symptoms; Aalbers, McNally, Heeren, Wit, & Fried, 2019). However, our review of MH literature reveals that none of the prominent risk and resilience factors (e.g., self-esteem, loneliness, social capital) is integrated into current conceptual models of PTH or PWB.…”
Section: Measuring Mental Healthmentioning
confidence: 99%
“…Following the screening procedure, 64 patients were enrolled in the study and thus participated in the ESM assessment. Of this sample, we only included data from participants providing over 21 valid responses (i.e., 1/3 of potential total number of responses); a cutoff based on prior research combining network analysis and ESM methodology (Aalbers et al, 2019;Greene et al, 2019). The resulting 23 participants who were included in the analyses (82.6% females) completed an average of 28.48 measurements (SD = 6.58).…”
Section: Participantsmentioning
confidence: 99%